Reducing Socio-economic Disparities in Indonesia: Strengthening the Taxation Sector in Indonesia - Kartiko, Nafis Dwi; Widjiastuti, Agustin (Universitas PGRI Madiun, 2023)
This legal research aims to analyze the strengthening of the tax sector in Indonesia to overcome the socio-economic disparities in the era of the Industrial Revolution 4.0. The research methodology used is descriptive qualitative research using a normative legal approach and documentary data collection techniques. The research model focuses on analyzing tax policy and related literature to understand the problem and provide solutions to address the problem. This research identifies tax evasion and corruption in the tax sector as the main factors contributing to Indonesia's low tax revenue. This research suggests that tax law reform and institutional transformation are needed to strengthen the capacity of tax institutions and improve tax administration, human resources, and information technology infrastructure to increase tax revenue and reduce tax evasion practices. Increased public confidence in the tax system can improve tax fairness and equity at all levels of society.